Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1002/jcp.25256
|View full text |Cite
|
Sign up to set email alerts
|

Fusion Pore Size Limits 5-HT Release From Single Enterochromaffin Cell Vesicles

Abstract: Enterochromaffin cells are the major site of serotonin (5-HT) synthesis and secretion providing ∼95% of the body's total 5-HT. 5-HT can act as a neurotransmitter or hormone and has several important endocrine and paracrine roles. We have previously demonstrated that EC cells release small amounts of 5-HT per exocytosis event compared to other endocrine cells. We utilized a recently developed method to purify EC cells to demonstrate the mechanisms underlying 5-HT packaging and release. Using the fluorescent pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…This study investigated the nutrient‐sensing capabilities of EC cells from the mouse GI tract. This is the first report of the enrichment of primary EC cells from the duodenum and colon of mice and builds on the capacity for primary EC cell purification in humans and guinea pigs . This approach allows for a paired comparison of gene expression in EC cells obtained from both regions within the same mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study investigated the nutrient‐sensing capabilities of EC cells from the mouse GI tract. This is the first report of the enrichment of primary EC cells from the duodenum and colon of mice and builds on the capacity for primary EC cell purification in humans and guinea pigs . This approach allows for a paired comparison of gene expression in EC cells obtained from both regions within the same mice.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first report of the enrichment of primary EC cells from the duodenum and colon of mice and builds on the capacity for primary EC cell purification in humans and guinea pigs. 14,22,33 This approach allows for a paired comparison of gene expression in EC cells obtained from both regions within the same mice. We have identified that EC cells enriched from the mouse duodenum and colon express receptors and transporters capable of sensing luminal sugars and FFAs, which have previously been linked to 5-HT release.…”
Section: Discussionmentioning
confidence: 99%
“…) and that both Vesicular monoamine transporter and the vesicular H + ‐ATPase pump regulate vesicle loading (Raghupathi et al . ). While it was demonstrated that 5‐HT is released from EC cells via exocytosis in a Ca 2+ ‐dependent manner similar to other endocrine cells, EC cells release surprisingly small amounts of 5‐HT given it is contained in large dense core vesicles (Raghupathi et al .…”
Section: Serotonin‐secreting Enteroendocrine Cells Display Unique Relmentioning
confidence: 97%
“…Some mechanistic insight into the mechanisms governing such small amounts of EC cell 5‐HT release has begun to emerge, and indicate that a smaller diameter fusion pore is able to limit the amount of 5‐HT released per fusion event (Raghupathi et al . ). How fusion pore control differs in these cells compared to other endocrine cells remains unknown.…”
Section: Serotonin‐secreting Enteroendocrine Cells Display Unique Relmentioning
confidence: 97%
“…Kiss-and-Run Fusion Pore Kinetics Are Independent of the Vesicle Matrix By definition, modes of release (sub-quantal versus quantal) are different from modes of vesicle fusion (kiss-and-run versus FFL) because kiss-and-run fusion may produce either quantal (ATP) or sub-quantal (CA) events (Figure 4). To determine whether CgA KD affected SOM-induced fusion pore flickering (or kissand-run) , we assessed fusion pore size during exocytosis-endocytosis using two nano-particle dextrans of different molecular weights and sizes (10 kDa and 40 kDa or 5 nm and 9 nm in diameter) Fulop et al, 2005;Raghupathi et al, 2015), given that SOM-induced endocytosis takes up only 5-nm but not 9-nm dextran in CgA WT cells. CgA KD did not affect the original patterns of SOM-induced uptake of both dextrans, and membrane fusion (kiss-and-run or fusion pore flickers) was not altered by CgA KD (Figure 6).…”
Section: Ca and Atp Release From A DCV Is Differentially Regulated Bymentioning
confidence: 99%